Development as a social fact - Andrew Schrank (economic sociology. perspectives and conversations, 2024)
This paper challenges both mainstream notions of development, which treat it as an objective feature of self-contained societies, and constructivist alternatives, which view it as an ethnocentric product of western imperialism. Instead, I argue that development is a social fact that's "not always so clearly discernible," much like the systems of "economic organization" alluded to by Durkheim in The Rules of Sociological Method (Durkheim [1895] 1982, 57), and go on to explore the implications for economic sociology.
Keywords: 300